BENEFITS OF DAILY READING - Ibrohim Mahmudov; Rahmatova E’zoza (TADQIQOTLAR, 2025)
Annotation: This article explores the extensive benefits of daily reading, the methods to build and sustain a reading habit, and the profound impact it has on personal, professional, and intellectual growth. It provides insights into how reading shapes individuals and its importance in an ever-changing world.